Development Of Android Application Based Learning Media In The Study Program Of Library And Information UIN Sulthan Thaha Saifuddin Jambi - Sigit hartono; M.A. Ade Saputra (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2020)
Learning media is one of the important supporting factors in achieving learning objectives. Learning media should have an attractive appearance, easy to use, and can be used anytime and anywhere so that it can stimulate student interest in learning. The purpose of this research is to develop learning media in the form of an android application in the Library Science Study Program. This research is a research and design research which consists of three stages, namely product analysis, product development, and testing. At the trial stage, the measuring instrument used was a questionnaire. The assessment of the feasibility of the application was carried out on one media expert, one material expert, and trials on 40 students. The assessment of the feasibility of the application and trial using a questionnaire which was then analyzed descriptively quantitatively. The results of the study obtained that the learning media based on the android application was very feasible to use with the results of an assessment score from media experts 83.92%, an assessment score from material experts 84.21%, and the results of trials conducted on 40 students got a score of 81.49%. It is hoped that this application can be used as a learning medium. In addition, it is hoped that further development will be carried out so that this application can be used on various platforms not only on Android.